Costs of post-stroke dysphagia during acute hospitalization from a health-insurance perspective. (March 2023) - Labeit, Bendix; Kremer, Almut; Muhle, Paul; Claus, Inga; Warnecke, Tobias; Dziewas, Rainer; Suntrup-Krueger, Sonja
Purpose: Oropharyngeal dysphagia is a common and complication-prone symptom after stroke and is assumed to increase medical expenses. The purpose of this study was therefore to examine acute hospitalization costs associated with post-stroke dysphagia. Method: This retrospective study included patients with acute stroke who had been examined by Flexible Endoscopic Evaluation of Swallowing (FEES). Health insurance expenditures were determined for the patient cases according to the 2021 revenue criteria. Multiple linear regression was used to examine predictors of health insurance spending including age, sex, stroke severity, stroke characteristics, comorbidity, therapeutic interventions, duration of artificial ventilation, length of hospital stay, and severity of dysphagia, as assessed by the Fiberoptic Endoscopic Dysphagia Severity Scale (FEDSS), ranging from 1 (best) to 6 (worst). Findings: Six hundred seventy four patients (men/women: 367/307; mean age: 71.1 ± 12.8 years; mean National Institute of Health Stroke Scale: 11.2 ± 6.2; FEDSS 1/2/3/4/5/6: 113/73/144/119/124/101; mean health-insurance costs 11, 521.5 ± 12, 950.5€) were included in the analysis. Advanced age ( p  = 0.007; B  = 57.6), catheter interventions ( p  < 0.001; B  = 4105.6), tracheotomy ( p  = 0.006; B  = 5195.2), duration of artificial ventilation ( p  < 0.001; B  = 388.6), length of hospital stay ( p  < 0.001; B  = 441.9), and severe dysphagia with an FEDSS of 6 ( p  = 0.004, B  = 2554.3) were independent predictors of increased health insurance expenditures ( p  < 0.001, R-squared = adjusted-R-squared = 0.83). Discussion and conclusion: The results of this study show an association between severe dysphagia and health care costs for acute hospitalization from a health-insurance perspective. Therefore, therapies that target severe dysphagia with impaired secretion management may have the potential to reduce costs.